2014
DOI: 10.1590/0104-07072014000240014
|View full text |Cite
|
Sign up to set email alerts
|

Health care for people with amputation: analysis from the perspective of bioethics

Abstract: A qualitative, descriptive and exploratory study was conducted through semi-structured interviews with 18 people undergoing amputation in the period 2008-2010, in public hospitals in Florianópolis. The objectives were to analyze the care provided by health professionals throughout the amputation process in the perspective of the amputee patient; and discuss the process of health care to the person with amputation in the bioethical analysis perspective. Data were analyzed according to content analysis. Three th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
(18 reference statements)
0
6
0
3
Order By: Relevance
“…Rodrigues (2011) also stresses the need for physicians to establish a dialogue with patients, considering that physicians are the protagonists in hospital settings and should be the first to embrace the distress of patients. The patients addressed by Marques et al (2014) also reported that there was no relationship with their physicians during hospitalization because they did not receive the information they need in regard to what was happening to their bodies. The need for such a relationship is highlighted by Batista and Luz (2012), who concluded that some patients tend to transfer their responsibilities to the physician and depend on their consent to perform certain tasks, therefore, it is necessary that a relationship be established between the physician and patient to answer all the questions patients might have.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Rodrigues (2011) also stresses the need for physicians to establish a dialogue with patients, considering that physicians are the protagonists in hospital settings and should be the first to embrace the distress of patients. The patients addressed by Marques et al (2014) also reported that there was no relationship with their physicians during hospitalization because they did not receive the information they need in regard to what was happening to their bodies. The need for such a relationship is highlighted by Batista and Luz (2012), who concluded that some patients tend to transfer their responsibilities to the physician and depend on their consent to perform certain tasks, therefore, it is necessary that a relationship be established between the physician and patient to answer all the questions patients might have.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument most frequently used in the qualitative studies (5) was the semistructured interview with content analysis (Gabarra and Crepaldi, 2009;Marques et al, 2014;Sales et al, 2012;Seren & Tilio, 2014;Vargas et al, 2013). Two studies report reflections on psychoanalytic theories (Carvalho, Serra, & Guimarães, 2011;Galván & Amiralian, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the moment that the problem occurs, we are in a condition of being violated, one that has a condition that requires more attention and readaptation in order to have wellbeing. 11 It is up to the professionals, who are links between public policy and those assisted by it, to minimize disparities that may arise amid present vulnerability, 14 independent from the one in need.…”
Section: Discussionmentioning
confidence: 99%